Effects of urban noise variability on cognitive abilities in indoor spaces: Gender differences. (November 2021) - Masullo, Massimiliano; Ruggiero, Gennaro; Alvarez Fernandez, Daniel; Iachini, Tina; Maffei, Luigi
Previous evidence has shown that exposure to urban noise negatively influences some cognitive abilities (i.e. verbal fluency and delayed recall of prose memory) of people in indoor spaces. However, long-standing literature in the cognitive domain has reported that men and women can show different performance on cognitive tasks. Here, we aimed to investigate if and how different patterns of perceived urban noises in indoor environments could affect male and female participants' cognitive abilities. Ambisonic sound recordings representing scenarios with varying noise patterns (low, medium and high variability) were acquired with an open window at three dwellings in a southern Italian city. As a control condition, the recordings were caught inside a quiet room. While exposed to theses four auditory conditions, participants had to perform cognitive tasks assessing free verbal memory recall, auditory–verbal recognition and working memory. The results show that male and female participants have a different tolerance to noise patterns. Women overperform men on verbal tasks, while the contrary effect emerges with men outperforming women on visuospatial working memory tasks.